A Comprehensive Overview on COVID-19: Future Perspectives - Rana, Rashmi; Tripathi, Ankit; Kumar, Naveen; Ganguly, Nirmal Kumar (Frontiers in Cellular and Infection Microbiology, 2021)
The outbreak of COVID-19 has proven to be an unprecedented disaster for the whole world. The virus has inflicted billion of lives across the globe in all aspects—physically, psychologically, as well as socially. Compared to the previous strains of β-CoV genera- MERS and SARS, SARS-CoV-2 has significantly higher transmissibility and worst post-recovery implications. A frequent mutation in the initial SARS-CoV-2 strain has been a major cause of mortalities (approx. 3 million deaths) and uncontrolled virulence (approx. 1 billion positive cases). As far as clinical manifestations are concerned, this particular virus has exhibited deleterious impacts on systems other than the respiratory system (primary target organ), such as the brain, hematological system, liver, kidneys, endocrine system, etc. with no promising curatives to date. Lack of emergency treatments and shortage of life-saving drugs has promoted the repurposing of existing therapeutics along with the emergence of vaccines with the combined efforts of scientists and industrial experts in this short span. This review summarizes every detail on COVID-19 and emphasizes undermining the future approaches to minimize its prevalence to the remaining lives.